2019
DOI: 10.3390/su11215896
|View full text |Cite
|
Sign up to set email alerts
|

Kuznets Environmental Curve for Ecuador: An Analysis of the Impact of Economic Growth on the Environment

Abstract: In the present investigation, an analysis of the impact of economic growth on the environment during the period 1971-2015 in Ecuador was made. The hypothesis of the environmental Kuznets curve was used as a study tool. We estimated this relationship in a country with strong dependence on revenues from the exploitation of natural resources and a low level of industry participation in gross domestic product (GDP). To generate empirical evidence, the methodology of the third degree Almon polynomial was applied wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Therefore, there is a need for closer international cooperation in this area. Many studies also confirmed the existence of relationships consistent with the environmental Kuznets curve-i.e., the dependence of environmental impact on the level of economic development of the country [60][61][62][63][64]. However, in developing countries, there are differences in the relationship between economic growth in energy use and renewable energy.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is a need for closer international cooperation in this area. Many studies also confirmed the existence of relationships consistent with the environmental Kuznets curve-i.e., the dependence of environmental impact on the level of economic development of the country [60][61][62][63][64]. However, in developing countries, there are differences in the relationship between economic growth in energy use and renewable energy.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, energy consumption has further been divided into renewable and nonrenewable energy consumption. The studies, for instance, Zhang et al (2009), Wang et al (2019a, b), Sadorsky (2009), Bildirici (2016), He and Kammen (2014), Papież et al (2018), Bildirici and Ersin (2015), Jimenez et al (2019), He et al (2017), Alvarado et al (2019), andShahbaz et al (2018), analyzed a positive association of economic growth on renewable energy consumption. Table 1 shows the potential determinants of energy consumption.…”
Section: Determinants Of Energy Consumptionmentioning
confidence: 99%
“…En particular, la CKA es una herramienta relevante para capturar la relación entre niveles medidos de indicadores de calidad ambiental con el desarrollo económico reflejado en el ingreso per cápita (Halicioglu, 2009). La hipótesis CKA sostiene la existencia de deterioro ambiental a niveles bajos de desarrollo económico, y luego a partir de cierto ingreso per cápita, un mayor crecimiento y desarrollo económico dan como resultado mejoras en la calidad ambiental (Jiménez et al, 2019;Jardón et al, 2017).…”
Section: Curva De Kuzntes Ambiental Y Determinantes De Las Emisionesunclassified
“…Aun así, este trabajo no considera el rol de otros posibles determinantes como la apertura comercial o el precio del petróleo. Jiménez et al (2019) brindan un análisis del impacto del crecimiento económico sobre el medio ambiente durante el período 1971-2015, utilizando la hipótesis CKA. Encuentran que la hipótesis se cumple, junto con una relación directa y positiva a corto plazo entre el crecimiento económico y las emisiones de CO2.…”
Section: Curva De Kuzntes Ambiental Y Determinantes De Las Emisionesunclassified